Self-stigma among parents of children with autism spectrum disorder in Vietnam - Loan, Khanh Thi; Lan Anh, Nguyen; Binh, Dinh Thi Hai; Lan Anh, Mai Thi (Tạp chí Nghiên cứu Y học, 2025)
This qualitative study was conducted to explore self-stigma among 11 parents of children with autism spectrum disorder receiving treatment at the National Children’s Hospital and five special education centers in Hanoi. Self-stigma was assessed through in-depth interviews using an interview guide with a semi-structured questionnaire of 5 open-ended questions. Findings from these interviews indicated that many parents experienced negative emotions when raising children with autism spectrum disorder, felt embarrassed of their children’s behavior and actively avoid social interactions. The study emphasizes the importance of implementing educational intervention programs to reduce self- stigma in this group.